Analysis of STEAM Content on the Module of Pancasila Student Profile Strengthening Project (P5) Based on Sasak Heritage - Iva Nurmawanti; Nurwahidah Nurwahidah; Setiani Novitasari; Anindita Suliya Hangesti Mandra Kusuma (Postgraduate, University of Mataram, 2023)
This study aims to analyze the STEAM content on the P5 module-based on Sasak Heritage. This research uses content analysis research and literature review. Content analysis was used to analyze the integration between STEAM and P5 in the modules that have been developed. Furthermore, this analysis was also strengthened by conducting a literature review on the STEAM topic from articles in international journals published starting in 2017-2022. The articles analyzed were 7 articles. The results obtained are that STEAM content at the P5 module stage can be made in 5 ways in implementing STEAM, namely by inter-discipline STEAM, several STEAM disciplines, as well as all STEAM disciplines at each stage of the planned project. STEAM integration can also be carried out starting at the basic education unit level with the application of P5